Primary Renal Angiosarcoma with Extensive Necrosis: A Difficult Diagnosis - Sohail Qayyum; Jignesh G. Parikh; Nadeem Zafar (Hindawi Limited, 2014)
Angiosarcoma of the kidney is an exceedingly rare and aggressive neoplasm. Very few cases have been reported in the English literature to date. We report a case of primary renal angiosarcoma with extensive necrosis and discuss its diagnostic difficulties. An 86-year-old male presented with a 12 cm necrotic renal mass and multiple pulmonary and hepatic nodules. A CT guided renal biopsy revealed extensive necrosis and few vascular channels lined by malignant endothelial cells. Diagnosis was given on a morphologic base and proven by an immunohistochemical study. Primary renal angiosarcoma should be included among the differential diagnosis of necrotic renal lesions.